Peer-feedbank in improving writing skills: perceptions of teachers and second-year non-English major students at Hanoi University of Business and Technology = Người học chữa bài cho người học trong phát triển kỹ năng viết: nhận thức của giáo viên và sinh - Trịnh, Thị Thanh Xuân (ĐHNN, 2017)
Chapter 1: Introduction-briefly presentsthe rationale, the aims, research questions, scope as well as the significance and organization of the study. Chapter 2: Literature review-discusses the literature related to the feedback in writing, types of feedback to students’ writing, advantages and disadvantages of doing peer written feedback in the teachingand learning of writingas well as the guiding principles for effective peer written feedback. Chapter 3: The methodology-describes the current situation of the teaching and learning writing at HUBT and the methodology dealing with the participants, instrumentation, data collection procedure and data analysis procedure. Chapter 4: Data Presentationand Discussion-analyzes and discusses the data then draws the implications for the teaching and learning of writing using peer written feedback. Chapter 5: Conclusion-summarizes the main findings of the study, states its limitations and offers suggestions for further study